The Implementation of the Concept of Social Living in Qur'an Surah Al-'Alaq Verses 1–5 from the Perspective of Tafsir Al-Munir in the Batu Putik Village Community - Muhammad Muhsana Efendi; Aria Panji Saputra (ISLAMIKA, 2026)
Although Qur'anic social ethics have been widely discussed in Islamic studies, limited empirical research has examined the concept of social living in Surah Al-‘Alaq verses 1–5 from the perspective of Tafsīr al-Munīr and its implementation within contemporary Muslim communities. This study aims to analyze the concept of social living contained in these verses, examine its implementation within the Batu Putik Village community, and identify the factors that support and influence its application in everyday social life. This study employed a qualitative descriptive design involving 20 participants selected through purposive sampling, including village officials, religious leaders, community leaders, youth representatives, women’s groups, and community members. Data were collected through observation, semi-structured interviews, and documentation and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that Tafsīr al-Munīr conceptualizes social living through interconnected values of literacy, knowledge acquisition, human dignity, social ethics, responsibility, cooperation, and community development. These values are implemented through Qur'anic learning activities, knowledge-sharing practices, mutual respect, deliberative decision-making (musyawarah), active community participation, gotong royong, and social assistance programs. The findings further indicate that religious values, leadership, family support, educational activities, and institutional initiatives serve as key supporting factors, while modernization, technological development, and variations in religious understanding influence the sustainability of these values. This study concludes that Surah Al-‘Alaq verses 1–5 integrate literacy, ethics, and social responsibility as foundations of social cohesion and community welfare. Its contribution lies in extending Qur'anic social ethics discourse and providing practical insights for strengthening socially responsible Muslim communities.